Analisis Semi-Kuantitatif Kandungan Logam Berat pada Air Minum Isi Ulang di Kecamatan Sail, Kota Pekanbaru Menggunakan Metode Test Kit - Reggyna Putri Januari; Alizar Ulianas (Lembaga Yasin AlSys, 2026)
Refill drinking water is widely consumed by the public because it is considered practical and economical, but its quality needs to be monitored, particularly regarding the possibility of heavy metal contamination that may affect health. This study aimed to analyze the heavy metal content of refill drinking water in Sail Subdistrict, Pekanbaru City, using a semi-quantitative method based on a test kit. The research samples were taken from five refill drinking water depots with the codes A1, A2, A3, A4, and A5. Testing was conducted using a heavy metal test kit that works based on color changes as an indicator of the presence of contaminants. The test results showed that all samples were still below the threshold, with the metal concentrations detected in each sample indicating no significant contamination. These findings indicate that refill drinking water in Sail Subdistrict, Pekanbaru City, is relatively safe for consumption in terms of heavy metal content. Thus, the test kit method can be used as a rapid and practical initial screening tool in monitoring the quality of refill drinking water, particularly for detecting the potential for heavy metal contamination in a simple manner before more in-depth laboratory testing is conducted.